2011
DOI: 10.1016/j.bbrc.2011.02.039
|View full text |Cite
|
Sign up to set email alerts
|

Procarcinogenic effects of cyclosporine A are mediated through the activation of TAK1/TAB1 signaling pathway

Abstract: Cyclosporine A (CsA) is an immunosuppressive drug commonly used for maintaining chronic immune suppression in organ transplant recipients. It is known that patients receiving CsA manifest increased growth of aggressive nonmelanoma skin cancers. However, the underlying mechanism by which CsA augments tumor growth is not fully understood. Here, we show that CsA augments the growth of A431 epidermoid carcinoma xenograft tumors by activating tumor growth factor β-activated kinase1 (TAK1). The activation of TAK1 by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 22 publications
3
18
0
Order By: Relevance
“…CsA treatment significantly increased the levels of proliferation markers cyclin D1 and proliferating cell nuclear antigen (PCNA) as compared to vehicle-treated control group (Figure 2A and B) confirming our earlier observation [16, 19]. However, administration of inhibitors of p38 or Akt alone or in combination to CsA-treated animals significantly decreased the expression of these proteins (Figure 2A and B and Suppl.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…CsA treatment significantly increased the levels of proliferation markers cyclin D1 and proliferating cell nuclear antigen (PCNA) as compared to vehicle-treated control group (Figure 2A and B) confirming our earlier observation [16, 19]. However, administration of inhibitors of p38 or Akt alone or in combination to CsA-treated animals significantly decreased the expression of these proteins (Figure 2A and B and Suppl.…”
Section: Resultssupporting
confidence: 89%
“…We also showed that CsA by regulating TGFβ-dependent signaling pathway promotes EMT and modulate invasive potential of cutaneous SCCs [16]. In this regard, our studies further demonstrated an involvement of TAK1/TAB1 signaling pathway, which by regulating MAPK and Akt augment cancer cell survival [19]. Here, we demonstrated that combined inhibition of p38 and Akt signaling pathways abrogates CsA-mediated cancer progression.…”
Section: Resultssupporting
confidence: 63%
See 2 more Smart Citations
“…With respect to skin cancer, CNIs have inhibitory effects on p53 and E-cadherin (tumor suppressors) which permit keratinocyte transformation and skin carcinogenesis [70]. Additionally, CNIs inhibit the DNA repair required to prevent transformation of UV damage to carcinogenesis, which implies a CNI-dependent oncogenic synergy between UV skin damage and immunosuppression [71].…”
Section: Post-transplant Patients Developing Warts and Carcinomasmentioning
confidence: 99%